Comprehensive Analysis Reveals the Potential Regulatory Mechanism Between Ub–Proteasome System and Cell Cycle in Colorectal Cancer - Zhang, Zhiyuan; Chen, Jingwen; Tang, Wentao; Feng, Qingyang; Xu, Jianmin; Ren, Li (Frontiers in Cell and Developmental Biology, 2021)
Ub-proteasome system (UPS) is an important regulatory component in colorectal cancer (CRC), and the cell cycle is also characterized to play a significant role in CRC. In this present study, we firstly identified UPS-associated differentially expressed genes, and all the differentially expressed protein-coding genes in CRC through 3 times differential analysis. UPS-associated genes were also further analyzed via survival analysis. WGCNA was used to identify the cell cycle-associated genes. We used protein-protein interaction (PPI) network to comprehensively mine the potential mechanism of the UPS-cell cycle regulatory axis. Moreover, we constructed a signature based on UPS-associated genes to predict the overall survival of CRC patients. Our research provided a novel insight view of the UPS and cell cycle system in CRC.